The research on wing sail of a land-yacht robot. (18th December 2015) - Xie, Shaorong; Chen, Jiqing; Li, Hengyu; Luo, Jun; Pu, Huayan; Peng, Yan
A wind-driven land-yacht robot which will be applied in polar expedition is presented in this article. As the main power of robot is provided by wing sail, improving the efficiency of wing sail is the key for its motion. Wing sail is composed of airfoil, so airfoil theory is researched first, and then several airfoils and their aerodynamic performance are compared, and a high-efficiency airfoil is selected. After that, overturning torque and start wind speed of robot are analyzed to determine the size of the wing sail. At last, the wing sail is manufactured and checked, and it is tested by start wind speed experiments, running speed experiments, steering motion, and obstacle avoidance experiments. The minimum start wind speed is 6 m/s. When wind speed is 10.3 m/s and angle of attack is 90°, running velocity of robot is 1.285 m/s. A land-yacht robot can run steering motion well and avoid obstacle to the target. The result shows that wing sail satisfies the motion requirement of land-yacht robot.